2020
DOI: 10.1101/2020.10.06.20208033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mask mandates can limit COVID spread: Quantitative assessment of month-over-month effectiveness of governmental policies in reducing the number of new COVID-19 cases in 37 US States and the District of Columbia

Abstract: Introduction: SARS-CoV-2 is the beta-coronavirus responsible for COVID-19. Facemask use has been qualitatively associated with reduced COVID-19 cases, but no study has quantitatively assessed the impact of government mask mandates (MM) on new COVID-19 cases across multiple US States. Data and Methods: We utilized a non-parametric machine-learning algorithm to test the a priori hypothesis that MM were associated with reductions in new COVID-19 cases. Publicly available data were used to analyze new COVID-19 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The dates of the Mask Mandates' implementation were obtained from the COVID-19 US State Policy (CUSP) Database 57 . Mask Mandates for All Public Facing Employees were used, as in previous reports 4,15 .…”
Section: Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…The dates of the Mask Mandates' implementation were obtained from the COVID-19 US State Policy (CUSP) Database 57 . Mask Mandates for All Public Facing Employees were used, as in previous reports 4,15 .…”
Section: Hypothesesmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of Governmental Mask Mandates promoting the wearing of face masks in public 3 , in reducing infections 4,5,6,7,8,9,10,11,12,13,14 , and reducing mortality 15,16 , associated with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also studying US states, Maloney et al . (2020) [24] find no statistically significant change in cases following mandate implementations.…”
Section: Introductionmentioning
confidence: 99%